The effect of education on health: Evidence from national compulsory schooling reforms - Raquel Fonseca; Pierre-Carl Michaud; Yuhui Zheng (SERIEs - Journal of the Spanish Economic Association, 2020)
This paper sheds light on the causal relationship between education and health outcomes. We combine three surveys (SHARE, HRS and ELSA) that include nationally representative samples of people aged 50 and over from fourteen OECD countries. We use variation in the timing of educational reforms across these countries as an instrument for education. Using IV-probit models, we find causal evidence that more years of education lead to better health. One additional year of schooling is associated with 6.85 percentage points (pp) reduction in reporting poor health and 3.8 pp and 4.6 pp reduction in having self-reported difficulties with activities of daily living (ADLs) and instrumental ADLs, respectively. The marginal effect of education on the probability of having a chronic illness is a 4.4 pp reduction. This ranges from a reduction of 3.4 pp for heart disease to a 7 pp reduction for arthritis. The effects are larger than those from a probit model that does not control for the endogeneity of education. However, we do not find conclusive evidence that education reduces the risk of cancer, stroke and psychiatric illness.
Keywords: I01; I02; 330; Education; Health; Causality; Compulsory schooling laws